Micro-thermoelectric devices with large output power fabricated on a multi-channel glass template. (16th October 2018) - Su, Ning; Guo, Shuai; Li, Fu; Liu, Dawei; Li, Bo; Li, Jingfeng; Ji, Muwei
Abstract: Micro-TE (thermoelectric) devices have received increasing attention because of their promising applications as energy resources for micro-systems. However, poor performance and complicated fabrication process has limited their application. This work demonstrates that micro-TEGs (thermoelectric generators) with a large output power of 218 μ W and output voltage of 34.7 mV under a larger temperature difference of 98 K can be fabricated using electro-deposition based on the multi-channel glass template, which is much higher than that of other reported work. The micro-TEGs consisted of four pairs of thermocouples. Each thermocouple was composited by about 200 p-type legs of Sb2 Te3 and 200 n-type legs of Bi2 Te3 60 μ m in diameter and 200 μ m in height, and were well filled in the glass template by impulse voltage deposition. The length of the TE legs can be adjusted by increasing the length of the channel, which led the large temperature difference and high output power and output voltage. Additionally, the glass template which shows low thermal conductivity and is electrically insulating, can be retained after being filled with TE materials, which simplifies the device fabrication process and also helps to enhance the rigidity of the TE modules. Moreover, this work also reveals that the output voltage can be further improved by increasing the numbers of thermocouples via decreasing the numbers of legs in each thermocouple.